Republic of Uganda Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank (Washington, DC, 2015)
This second Report on the Observance of Standards and Codes (ROSC) Accounting and Auditing (A&A) assesses the degree to which the findings and policy recommendations of the first review have been implemented. The report identifies and assesses issues that have emerged after the first review. From these assessments, the World Bank team identifies the root causes of failure to implement the proposed recommendations. It makes policy recommendations aimed at further improving the quality of financial reporting, which should contribute to lowering the cost of borrowing and enhance private sector competitiveness; ultimately contributing to the attainment of Uganda s strategic objectives aimed at achieving; (i) inclusive and sustainable growth, (ii) job creation, and (iii) improved governance. These are themes in the 2012/2013 and 2013-2014 and Uganda National Budgets. Going forward, the above key policy recommendations should form the basis for a stakeholder driven Country Action Plan which should be regularly monitored to ensure it is effectively implemented. This will improve financial reporting in both the private and public sector and therefore play a role in enhancing transparency and accountability which are key ingredients in attracting private sector investors and thus lead to economic growth as well as improve on public service delivery.